2018
DOI: 10.3390/ijerph15102200
|View full text |Cite
|
Sign up to set email alerts
|

The Pertinence of Microwave Irradiated Coconut Shell Bio-Sorbent for Wastewater Decolourization: Structural Morphology and Adsorption Optimization Using the Response Surface Method (RSM)

Abstract: Palm oil mill effluent contains carcinogenic coloured compounds that are difficult to separate due to their aromatic structure. Though colour treatment using adsorption processes at lower pH (<4) have been reported effectual, due to its acidity the remediated effluent poses an environmental hazard as a result. Thus, the current study focused on achieving decolourization at neutral pH by enhancing the morphology of the coconut shell activated carbon (CSAC) using N2 as activating-agent with microwave irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…However, ponding system has being the most common method used for treating POME before discharge into the waterways but it has been proven ineffectual, particularly for color removal (Rana et al, 2017;Iskandar et al, 2018). Though physical and/or chemical treatment methods such as adsorption, chemical oxidation and reduction, precipitation, chemical-photolysis, and electrochemical processes decolorizes POME (Abdulsalam et al, 2018a), but they are economically unsustainable and often resulted in the generation of acidic secondary effluent which requires further treatment before discharge. Nonetheless, remediation of organic contaminants in POME using microorganisms such as fungus and bacteria, had demonstrated a promising performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, ponding system has being the most common method used for treating POME before discharge into the waterways but it has been proven ineffectual, particularly for color removal (Rana et al, 2017;Iskandar et al, 2018). Though physical and/or chemical treatment methods such as adsorption, chemical oxidation and reduction, precipitation, chemical-photolysis, and electrochemical processes decolorizes POME (Abdulsalam et al, 2018a), but they are economically unsustainable and often resulted in the generation of acidic secondary effluent which requires further treatment before discharge. Nonetheless, remediation of organic contaminants in POME using microorganisms such as fungus and bacteria, had demonstrated a promising performance.…”
Section: Introductionmentioning
confidence: 99%
“…The main application is the use of coconut as a bio-sorbent after an activation process (Burakov et al, 2018). The main advantages are the high availability of coconut (Abdulsalam et al, 2018), low cost of application (LH Nguyen et al, 2019), good adsorption performances and highly carbonaceous and stable structure (Abdulsalam et al, 2018). The adsorption performance can be attributed to the confined carbon density, the structural matrix of the precursors and their activation procedures (Abdulsalam et al, 2018).…”
Section: Residue Performancementioning
confidence: 99%
“…The main advantages are the high availability of coconut (Abdulsalam et al, 2018), low cost of application (LH Nguyen et al, 2019), good adsorption performances and highly carbonaceous and stable structure (Abdulsalam et al, 2018). The adsorption performance can be attributed to the confined carbon density, the structural matrix of the precursors and their activation procedures (Abdulsalam et al, 2018). For instance, Samanta et al (2018) found that treatments that caused the removal of hemicelluloses from coconut fibres were more effective and increased adsorption of the dyes.…”
Section: Residue Performancementioning
confidence: 99%
“…The adsorbent required for an adsorption process may be produced from different sources such as cellulose [19], soil [20], fly ash and coal [21], activated sludge [4], boron-selective resins [22], and coconut shell [23], among others. However, the adsorptive capacity relies on the intrinsic properties of the precursor, the carbonation-activation method, and the behavioral properties of the targeted adsorbate [24]. For example, Kluczka et al [25] conducted an adsorption study using gly-resin to eliminate boron from wastewater and recorded an optimum adsorption capacity of 1.6 mg/g, at pH 9.…”
Section: Introductionmentioning
confidence: 99%